Pencegahan Schistosomiasis Menggunakan Ekstrak Biji Pinang di Desa Alitupu: Prevention of Schistosomiasis Using Areca Nut Seed Extract in Alitupu Village - Handayani, Tien Wahyu; Triposa, Vivi Gretia; Asti, Nurul; Dewi, Ni Made Sinta (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Schistosomiasis is a disease condition that can be acute or chronic, caused by infection with Schistosoma blood worms from the genus Schistosoma. This disease is endemic in Central Sulawesi Province. Transmission occurs through water containing Schistosoma worm larvae (cercariae) and Oncomelania water snails. Hopefully, this service can educate the public about schistosomiasis and anticipate the prevention of schistosomiasis in Alitupu Village District. North Lore, Kab. Poso. Lectures were carried out in this community service activity, and satisfaction levels were calculated using 20 respondents. The instrument used for this service is a questionnaire. This service was carried out in Alitupu Village, District. North Lore, Kab. Poso, Central Sulawesi. The results of the community satisfaction assessment showed that, in general, partners were satisfied with the activities (85%) and community understanding (85%), and 85% of the material delivered was in line with community expectations and needs. Based on the results of community satisfaction, it can be concluded that the community is delighted (83.3%).